Influence of Botrytis cinerea (Helotiales: Sclerotiniaceae) infected leaves of Vitis vinifera (Vitales: Vitaceae) on the preference of Epiphyas postvittana (Lepidoptera: Tortricidae). Issue 1 (17th April 2014) - Rizvi, Syed Z M; Raman, Anantanarayanan; Wheatley, Warwick; Cook, Geoffrey; Nicol, Helen
Abstract Herbivorous insects use sensory cues to choose their host plants for feeding and/or oviposition by assessing host quality. Olfactory, contact and visual cues of the host mediate such choices. The right‐host choice for oviposition by a lepidopteran is essential for the performance of its progeny. In natural conditions, plants are often and concurrently attacked by both herbivorous insects and pathogenic fungi. In such a three‐way relationship, the interaction between the plant and insect is usually influenced by the fungal population, and such an influence can be either mutualistic or antagonistic. In the present study, we tested the three‐way relationship using the system, Epiphyas postvittana–Vitis vinifera–Botrytis cinerea. We sought answers to the questions: (1) whether the females of E. postvittana prefer to oviposit on V. vinifera leaves infected by B. cinerea; and (2) whether the larvae of E. postvittana prefer to feed on V. vinifera leaves infected by B. cinerea. We found that the host‐seeking gravid females of E. postvittana 'tested' the infection status of the host plant using olfactory, visual, and tactile cues; in consequence, they laid significantly fewer eggs on the moderately (30–60%) and intensely (90–100%) infected leaves of V. vinifera. The neonate larvae preferred to feed on mildly (5–10%) and moderately (30–60%) infected leaves, as against the uninfected (control) leaves, and showed no preference for intensely (90–100%) infected leaves. External and internal examination of the larvae established that the larvae fed on B. cinerea‐infected leaf because viable conidia of B. cinerea occurred on the body surface and within the gut of the neonate larvae.